An exploratory study into therapeutic alliance, defeat, entrapment and suicidality on mental health wards. Issue 2 (19th December 2017) - Dunster‐Page, C. A.; Berry, K.; Wainwright, L.; Haddock, G.
Accessible summary: What is known on the subject?: The strength of a relationship between people with mental health difficulties and professionals has been linked to patients feeling suicidal. A relationship has been found between how defeated and trapped people with mental health difficulties feel and how suicidal they feel. What this paper adds to existing knowledge?: This study explored the relationship between alliance, suicidality, defeat and entrapment in people admitted to mental health wards as previous research has focused on people in the community. Patient‐rated defeat, entrapment and suicidality are related in this sample of people admitted to mental health wards. A relationship was found between how well nurses said they bonded with their named patient and how trapped the patients felt by their environment. What are the implications for practice?: Nurses should consider if patients are feeling defeated or trapped when helping people with mental health difficulties to feel less suicidal. Abstract: Introduction: Suicidality is prevalent worldwide, particularly in people who access mental health services. The quality of therapeutic alliance between people with mental health difficulties and staff has been associated with suicidality but only in community settings. Defeat and entrapment are correlated with suicidality and may mediate any relationship between alliance and suicidality. Therefore, this exploratory study explored these relationships in people admitted to mental health wards. Aim: To explore defeat, entrapment, suicidality and alliance between nurses and people admitted to mental health wards. Method: Fifty inpatient nurse–patient dyads completed questionnaires regarding demographics, defeat, entrapment, suicidality and alliance with their named nurse. Nurses completed questionnaires on demographics, alliance with their patient and the patients' suicidality. Results: Defeat, entrapment and suicidality were correlated. A correlation between nurse‐rated bond and external entrapment was found, but no other correlations between alliance, defeat, entrapment and suicidality were statistically significant. Discussion and clinical implications: Ward‐based nurses should consider the relationship between defeat, entrapment and suicidality when developing interventions to improve suicidality. Although there was no evidence of a relationship between total alliance and suicidality, developing closer bonds with patients may reduce patients' feelings of being trapped by their environment.